Spatial Microsimulation for Rural Policy Analysis - O'Donoghue, Cathal.; Ballas, Dimitris.; Clarke, Graham.; Hynes, Stephen.; Morrissey, Karyn. (Advances in Spatial Science, The Regional Science Series,, 2013)
The aim of this book is to explore the challenges facing rural communities and economies and to demonstrate the potential of spatial microsimulation for policy and analysis in a rural context. This is done by providing a comprehensive overview of a particular spatial microsimulation model called SMILE (Simulation Model of the Irish Local Economy). The model has been developed over a ten year period for applied policy analyis in Ireland which is seen as an ideal study area given its large percentage of population living in rural areas. The book reviews the policy context and the state of the art in spatial microsimulation against which SMILE was developed, describes in detail its model design and calibration, and presents example of outputs showing what new information the model provides using a spatial matching process. The second part of the book explores a series of rural issues or problems, including the impacts of new or changing government or EU policies, and examines the contribution that spatial microsimulation can provide in each area.